Conceivable Design of a Wideband Unidirectional Antenna using Truncated Microstrip Patches for S-Band Applications - Hemachai, Thanaphon; Janpangngern, Pisit; Dentri, Sitthichai; Phongcharoenpanich, Chuwong (My University, 2025)
This paper presents the conceivable design of a wideband unidirectional antenna suitable for CubeSat applications operating in the S-band frequency ranges of 2.025-2.110 GHz (uplink band) and 2.200-2.290 GHz (downlink band). The antenna employs a truncated microstrip patch design combined with additional parasitic patches to achieve circular polarization. It is printed on an RT/duroid® 5880 substrate with a thickness of 0.6 mm and a relative permittivity of 2.2. The design consists of a central truncated radiating patch and four segment-circular parasitic patches, positioned near the edges of the substrate to enhance bandwidth and axial ratio performance, which is crucial for achieving circular polarization. The antenna is excited using a coaxial probe feed to ensure efficient energy transfer and proper impedance matching. Simulation results demonstrate that the antenna achieves a wide impedance bandwidth covering 1.80 GHz to 2.40 GHz with a reflection coefficient (|S11|) below -10 dB. The axial ratio remains below 3 dB across the frequency range of 2.025 GHz to 2.290 GHz, confirming circular polarization, with a minimum axial ratio of 1.34 dB at 2.25 GHz. Additionally, the antenna exhibits a stable gain of approximately 7.28 dBic at 2.15 GHz, making it suitable for CubeSat communication systems requiring reliable and efficient signal transmission. To further strengthen the contribution of this research, a performance comparison with existing CubeSat antennas is provided, along with a discussion of potential environmental impacts in space, such as temperature variations and radiation effects. Future work will focus on prototyping, experimental validation, and optimizing the antenna design for different mission scenarios, including scaling for other frequency bands and multi-antenna configurations.
Keywords: Axial ratio; Circular polarization; CubeSat communication; Truncated microstrip patch